2017
DOI: 10.1016/j.immuni.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus-Deficient Cervicovaginal Bacterial Communities Are Associated with Increased HIV Acquisition in Young South African Women

Abstract: Summary Elevated inflammation in the female genital tract is associated with increased HIV risk. Cervicovaginal bacteria modulate genital inflammation, however their role in HIV susceptibility has not been elucidated. In a prospective cohort of young, healthy South African women, we found that individuals with diverse genital bacterial communities dominated by anaerobes other than Gardnerella were at over 4-fold higher risk of acquiring HIV and had increased numbers of activated mucosal CD4+ T cells compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
713
9
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(801 citation statements)
references
References 33 publications
27
713
9
6
Order By: Relevance
“…Studies of the TFV film will need to assess whether the film delivery mechanism is capable of altering innate HIV immunity through changes to the mucin expression and the quantity of high mannose glycoproteins in the vaginal environment, as has also been suggested for the 1% TFV gel (41). Additionally, the TFV gel was shown to alter local microbial communities in the vagina, making women using these products more susceptible to bacterial dysbiosis and HIV acquisition through inflammatory pathways, and it will be important to explore similar associations for other topically applied HIV prevention products (15,18 ■ ,42). …”
Section: Text Of Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of the TFV film will need to assess whether the film delivery mechanism is capable of altering innate HIV immunity through changes to the mucin expression and the quantity of high mannose glycoproteins in the vaginal environment, as has also been suggested for the 1% TFV gel (41). Additionally, the TFV gel was shown to alter local microbial communities in the vagina, making women using these products more susceptible to bacterial dysbiosis and HIV acquisition through inflammatory pathways, and it will be important to explore similar associations for other topically applied HIV prevention products (15,18 ■ ,42). …”
Section: Text Of Reviewmentioning
confidence: 99%
“…However, it has recently been hypothesized that the efficacy of topically-applied PrEP products may be moderated by vaginosis dysbiosis, a general term indicating that vaginal microbiota are sub-optimal (13 ■■ ). This is a significant public health concern given that bacterial vaginosis (a condition diagnosed using microscopy and/or clinical criteria) is common in settings where HIV is highly prevalent and has been shown to significantly influence risk of HIV acquisition through inflammatory pathways (14,15,16 ■ ,17,18 ■ ,19 ■■ ). Specifically, vaginal dysbiosis can result in higher vaginal pH (due to lower concentrations of Lactobacillus species) and increased activated CCR5+ CD4+ T-cells in vaginal mucosa and pro-inflammatory cytokines in cervical secretions (15,16 ■ ,18 ■ ,19 ■■ ,20,21 ■ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both P. amnii and P. bivia have been associated with genital inflammation (Anahtar et al 2015;Gosmann et al 2017;Lennard et al 2017) and BV, yet in this study P. bivia levels did not differ by BV status or inflammation (Lennard et al 2017). Fettweis et al (2014) previously reported that P. amnii is more prevalent in African American women, compared to women of European ancestry, which may explain the high rates of P. amnii colonisation seen here.…”
Section: Bvmentioning
confidence: 51%
“…P. amnii sowel as P. bivia is met genitale inflammasie (Anahtar et al 2015;Gosmann et al 2017;Lennard et al 2017) en BV geassosieer. In hierdie studie het P. bivia-vlakke egter nie volgens BV-status of inflammasie verskil nie.…”
Section: Soi-voorkomssyfers (55%)unclassified